ADVANCED SYSTEMS FOR RELIABLE STORAGE OF BIOMEDICAL INFORMATION - H. Hristov; P. Batalov (Автоматизация технологических и бизнес-процессов)
Abstract. This article examines state-of-the-art systems and emerging technologies designed to ensure the reliable, long-term, and secure storage of biomedical information, especially in the context of the rapidly growing volume of healthcare-related data. It explores the full lifecycle of biomedical data management—from initial data acquisition through sensors, wearable devices, and IoT systems, to processes of validation, analysis, and secure long-term storage. Particular attention is given to the role of electronic health records (EHRs), which serve as the backbone of modern digital healthcare, enabling centralized storage of patient histories, diagnostic data, and treatment protocols.